The Relationship between Challenges of IoT Adoption and Supply Chain Performance among the Retailers in Kuala Lumpur - Wong Jia Qi,; Nor Kamariah Kamaruddin, (Research in Management of Technology and Business, 2024)
The IoT enables the retail industry to gain real-time insight into how it operates relative to it. IoT provides real-time data gathering, analysis, and communication by linking physical items and devices to the internet. The adoption of IoT comes with challenges that can significantly affect the supply chain performance. Although the adoption of IoT can improve supply chain performance, nevertheless there are still many obstacles to overcome. Issues such as limited study focusing on challenges of IoT adoption towards supply chain performance, lack of trust in technology and lack of relevant knowledge on IoT among retailers. Therefore, this research was conducted to examine the relationship between challenges of IoT adoption and supply chain performance among the retailers in Kuala Lumpur. This study encompasses a population of 71,433 individuals, specifically focusing on retailers in Kuala Lumpur. The survey necessitated a total sample size of 382 retailers in Kuala Lumpur for comprehensive data collection. Among the 382 sets of survey questionnaires distributed, 312 responses were received, reflecting a response rate of 81.68%. Based on the correlation analysis conducted in this study, it showed there was a positive relationship between organization adjustment and supply chain performance (r = 0.711). Moreover, there was also a positive relationship between trustworthiness of technology and supply chain performance (r = 0.731). This research study contributes to a deeper understanding of how challenges in IoT adoption can impact the performance of supply chains. Both academia and the retail industry stand to gain valuable insights from this research.